2017
DOI: 10.1016/j.jtho.2017.09.1966
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies and Prognostic Factors of Limited-Stage Primary Small Cell Carcinoma of the Esophagus

Abstract: Treatment modalities and N stage are independent prognostic factors. Radical esophagectomy should be considered as the primary treatment for stage I or IIA PSCCE, and nCT followed by esophagectomy could be an effective treatment option for stage III PSCCE. Multicenter randomized studies are required to confirm the role of nCT in the management of limited-stage PSCCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 40 publications
9
56
1
Order By: Relevance
“…However, the United States is one of the low‐incidence regions of esophageal cancer, and the most common pathological type is adenocarcinoma, originating mostly in the lower third of the esophagus . In the present study, in the Chinese SCCE group, patient age, sex, primary tumor location, and tumor length were similar to that of esophageal squamous cell carcinoma, in accordance with the results of previous reports from China . In contrast, the clinical features of SCCE patients in the U.S. group were more similar to that of adenocarcinoma .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the United States is one of the low‐incidence regions of esophageal cancer, and the most common pathological type is adenocarcinoma, originating mostly in the lower third of the esophagus . In the present study, in the Chinese SCCE group, patient age, sex, primary tumor location, and tumor length were similar to that of esophageal squamous cell carcinoma, in accordance with the results of previous reports from China . In contrast, the clinical features of SCCE patients in the U.S. group were more similar to that of adenocarcinoma .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the OS of the Chinese group was higher than that of the U.S. group, but the survival difference disappeared after PSM, suggesting that there was no significant difference in the prognosis of SCCE between the two groups if the disparities in patient age, sex, and VALSG stage were removed. Furthermore, previous studies have reported similar pathological features, immunohistochemical staining, and aggressive nature of SCCE among different worldwide populations , , , . Therefore, we concluded that SCCE from different populations should be analyzed as a single entity, though there might be discrepancies in the pathogenesis, demographics, and certain clinical features.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The common types of esophageal cancer are squamous cell carcinoma and adenocarcinoma and primary small cell carcinoma of the esophagus (PSCCE) which is a relatively rare histological subtype, accounting for only 0.5–2.8% of all esophageal malignant tumors . PSCCE is characterized by high aggression, early dissemination and poor prognosis . Although the first case was noticed by McKeown in 1952, the lower incidence of PSCCE made it is difficult to establish a standard treatment .…”
Section: Introductionmentioning
confidence: 99%